EVALUATION OF POSTOPERATIVE OUTCOMES FOLLOWING DECOMPRESSIVE CRANIECTOMY IN PATIENTS WITH INTRACRANIAL HYPERTENSION DUE TO SEVERE TRAUMATIC BRAIN INJURY - Samuel Djilas Ferreira de Abreu; Beatriz Fogagnoli Araujo de Almeida; Victor Gabino de Macedo; Gomes , Lara Nunes; Figueirêdo, Gustavo Furtado de; Nogueira, Assis Porfirio Furtado (Brazilian Journal of Implantology and Health Sciences, 2025)
Traumatic brain injury (TBI) is a major public health concern with significant neurological, social, and economic impacts. Decompressive craniectomy (DC) is a surgical intervention used to manage severe TBI with refractory intracranial hypertension (ICH), aiming to reduce mortality by alleviating intracranial pressure. Despite its life-saving potential, DC is associated with high rates of severe disability and long-term complications, including hydrocephalus and infections. This study aims to systematically analyze and compare the postoperative outcomes of decompressive craniectomy in patients with severe TBI, focusing on mortality, functional recovery, and complication rates. A systematic review was conducted using databases such as PubMed, MEDLINE, and SciELO, applying predefined inclusion and exclusion criteria. The search utilized keywords including "Decompressive Craniectomy," "Traumatic Brain Injury," "Intracranial Hypertension," and "Outcomes," combined with the Boolean operator "AND." The analysis revealed that decompressive craniectomy significantly reduces mortality compared to standard medical management but is associated with a higher incidence of vegetative states and severe disabilities. Early intervention appears to yield better neurological outcomes, while delayed surgery correlates with higher morbidity. The findings highlight the need for individualized treatment strategies and robust postoperative rehabilitation protocols to optimize patient recovery and quality of life. Decompressive craniectomy remains a critical intervention for severe TBI with ICH; however, careful patient selection and long-term follow-up are essential to balance survival benefits with quality of life considerations.